A well to wire LCA model development and sensitivity analysis for carbon footprint of combined cycle power plants in Iranian electricity network. Issue 5 (9th April 2017) - Dalir, Fatemeh; Shafiepour Motlagh, Majid; Ashrafi, Khosro
ABSTRACT: The present research introduces a well to wire pseudo comprehensive carbon footprint model for combined cycle power plants. The mentioned model integrates land use change model, operational model and transmission and distribution model into one comprehensive model. The parameters which their effects are considered in the integrated model are: fuel type, fuel transmission type, emission for fuel extraction and processing, own consumption of the plant, degradation, site ambient condition, transmission and distribution losses. For quantifying the effectiveness of each parameter, sensitivity analyses based on different life cycle scenarios are performed. The result shows that the effect of land use change is negligible. The carbon footprint of electrical energy produced in combined cycle plant until it is delivered to the end users varies from 321 to 522 g CO2 eq/kWh.